Особливості перебігу епілепсій у дітей і надання медичної допомоги цим дітям під час пандемії COVID-19 і воєнних дій в Україні - Танцура, Людмила Миколаївна; Пилипець, Олена Юріївна; Танцура, Євген Олександрович; Третьяков, Дмитро Володимирович; Лук'янцева, Ольга Юріївна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Епілепсія залишається одним із найпоширеніших неврологічних захворювань. Мета. Визначення особливостей перебігу епілепсії у дітей і надання їм медичної допомоги під час пандемії COVID-19 і воєнних дій в Україні. Матеріали та методи. Шляхом анонімного on-line анкетування з використанням оригінального опитувальника досліджено: під час пандемії COVID-19 – 107 родин, які мають дітей із епілепсією віком від 3 міс до 18 років, в період воєнних дій – 108 родин з дітьми з різними формами епілепсій віком від 1 до 18 років. Всі діти знаходилися під спостереженням у відділенні дитячої психоневрології і пароксизмальних станів ДУ «Інститут неврології, психіатрії та наркології ім. П. В. Волошина НАМН України. Отримані результати. Встановлено, що під час війни у дітей із епілепсією достовірно частіше відмічається як втрата контролю нападів (10,19 проти 0 %), так і збільшення їх частоти (41,8 проти 16,67 %). Підтверджені можливості надання медичної допомоги в кризові періоди на високому рівні, в тому числі – з широким застосуванням електронних засобів зв’язку. Всі необхідні питання стосовно перебігу епілепсії у дитини під час COVID-19 вдалося визначити в 90,65 % батьків та під час воєнних дій – у 86,11 %. Висновки. Виявлено, що розлади в психічній, емоційній, поведінковій сферах достовірно частіше відмічаються батьками в воєнний час, порівняно з періодом пандемії, що свідчить про доцільність/необхідність подальших досліджень цього спрямування. Epilepsy remains one of the most common neurological diseases. Children with chronic diseases and, in particular, children with epilepsy are one of the least protected categories of the population, which is due, firstly, to the peculiarities of epilepsy as a disease. It is well known that patients with this pathology require careful medical monitoring, timely examination and control, and continuous intake of vital medications, as well as the fact that the course of epilepsy is sensitive to factors such as acute and chronic stress, sleep deprivation, excessive photostimulation, intercurrent diseases and the adequacy of their treatment; and during global disasters, it intensifies and becomes completely unpredictable. Purpose of the study was to identify the peculiarities of epilepsy in children and provide them with medical care during the COVID-19 pandemic and military operations in Ukraine. Materials and methods. An anonymous online survey using the original questionnaire was conducted: during the COVID-19 pandemic – 107 families with children with epilepsy aged 3 months to 18 years, during the military operations – 108 families with children with various forms of epilepsy aged 1 to 18 years. All children were under observation at the Department of Pediatric Psychoneurology and Paroxysmal Conditions of the P. V. Voloshin Institute of Neurology, Psychiatry and Narcology of the National Academy of Medical Sciences of Ukraine. The results. It was found that during the war, children with epilepsy significantly more often have both a loss of seizure control (10.19 % vs. 0) and an increase in their frequency (41.8 vs. 16.67 %). The ability to provide high-level medical care during crisis periods, including with the widespread use of electronic means of communication, has been confirmed. All the necessary questions about the course of epilepsy in a child during COVID-19 were identified in 90.65 % of parents and during hostilities – in 86.11 %. Conclusions. It has been found that disorders in the mental, emotional, and behavioral spheres are significantly more frequently reported by parents in wartime compared to the pandemic period, which indicates the feasibility/necessity of further research in this area.
Peculiarities of the course of epilepsy in children and the provision of medical assistance to them during the COVID-19 pandemic and military actions in Ukraine
Keywords: діти; епілепсія; війна; пандемія COVID-19; children; epilepsy; war; COVID-19 pandemic